The Functional Outcome of Reconstruction of Anterior Cruciate Ligament Using Hamstring Autograft - Gaurav Arora; Avinash Singh; N C Arora; Mahipal Singh Sidhu; Puneet Kamra; Kuldeep Prakashchandra Pindaria (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Anterior cruciate ligament (ACL) tear is the most common knee ligament, which gets torn in sports activities. Nowadays, arthroscopic ACL reconstruction using autograft or allograft has become the standard mode of treatment with a good functional outcome. Objective: The objective of the study was to study the functional outcome of arthroscopic ACL reconstruction using quadrupled hamstring autograft. Materials and Methods: The study was conducted between 2019 and 2021 in the Department of Orthopedics at SGT Medical College and Hospital on 25 patients, who underwent arthroscopic ACL reconstruction using hamstring autograft. The functional outcome in these patients was assessed using IKDC and Lysholm knee scores, measuring preoperatively and postoperatively at 3-, 6-, and 12-month duration. Results: We found 88% of patients had a good-to-excellent functional outcome, and the rest had fair outcome. Conclusion: Arthroscopic ACL reconstruction using quadrupled hamstring autograft gives overall good functional outcomes.